How Can Universities Engage With Local Small Businesses? A Case Study of the Chemistry Innovation Laboratory - Jiang, Lijie (2013)
In a fast moving environment university-industry collaborations play a critical role in developing a knowledge-based economy and a sustainable competitive advantage. Knowledge transfer from university to industry is supported by national governments as part of their innovation, national growth and competitiveness program. The aim of this project is to develop a strategy that will re-energise the continuing efforts of the BPU in engaging with local chemical-using SMEs through the Chemistry Innovation Laboratory (CIL). The ultimate goal of the CIL extension will be to identify SMEs who are able and willing to form long-term partnerships with the School. This study will focus on the needs of SMEs, the problems facing in the collaboration between the BPU and SMEs, what the university can offer in order to meet the needs of SMEs, and how to improve BPU’s marketing strategy in engaging with SMEs. The interviewees involved in this study were selected from academics of the School of Chemistry and executive management committees of chemical using SMEs. The research findings are almost consistent with those in the literature. The University needs are complex and span longer timescales and SMEs tend to be focussed on short-term objectives to satisfy cash-flow and survive. This study discloses getting the right offer that moves from short-term opportunistic services to longer-term relationship building based around research-driven engagements that are repeat, longer term and align the strategic goals of University with SME and therefore the expectations of both academics and business owners. It was concluded from this research, to achieve the optimum engagement with SMEs. The BPU must utilise message and appropriate mediums for reaching SMEs and gaining their attention.